2017
DOI: 10.1093/jee/tox181
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ozone to Control Dried Fig Pests—Oryzaephilus surinamensis (Coleoptera: Silvanidae) and Ephestia kuehniella (Lepidoptera: Pyralidae)—and Its Organoleptic Properties

Abstract: Ozone is a powerful oxidant which can be used for killing insects and microorganisms. In this study, ozone was applied in the gaseous form to control two species of pests in stored dried figs. The samples of figs (50 g each) were infested with adults of Oryzaephilus surinamensis L. and larvae of Ephestia kuehniella Zeller and were subjected to different combinations of ozone concentrations (2, 3, and 5 ppm) and exposure times (15, 30, 45, 60, and 90 min). Changes in organoleptic properties (color, sweetness, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, they found that the adults of cowpea weevil and bean bruchid (Acanthoscelides obtectus (Say)) were more susceptible to the gas concentrations than Mexican bean weevil adults. In the research of Sadeghi et al [37], the ozone concentration of 2 ppm and time period of 15 min resulted in the lowest mortality of the adults of the sawtoothed grain beetle (Oryzaephilus surinamensis L.) and larvae of flour moth E. kuehniella, while the concentration of 5 ppm and time of 90 min led to complete mortalities. These findings, about the susceptibility of stored-products insect pests to CO 2 gas, supports the results of current investigation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, they found that the adults of cowpea weevil and bean bruchid (Acanthoscelides obtectus (Say)) were more susceptible to the gas concentrations than Mexican bean weevil adults. In the research of Sadeghi et al [37], the ozone concentration of 2 ppm and time period of 15 min resulted in the lowest mortality of the adults of the sawtoothed grain beetle (Oryzaephilus surinamensis L.) and larvae of flour moth E. kuehniella, while the concentration of 5 ppm and time of 90 min led to complete mortalities. These findings, about the susceptibility of stored-products insect pests to CO 2 gas, supports the results of current investigation.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, no significant impacts on the color, aroma, sweetness, sourness, brittleness, hardness, and general acceptance of the dried apricot were caused by enhancing the gas concentration of CO 2 . Similarly, Sadeghi et al [37] reported no significant influences of increasing ozone concentration and times of fumigation on the color, sweetness, sourness, brittleness, hardness, and general acceptance of dried figs and raisins, but they witnessed considerable effects on the aroma of the two products. Of course, they concluded that due to the volatility of ozone gas, their unpleasant odors could disappear over time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The feasibility of using ozone to kill insects has been established in dried fruits and nuts, e.g. Indian meal moth in pistachios, and Oryzaephilus surinamensis in dried figs . Ozone has potential to reduce the toxic effect of insecticides in food products by acting as a strong oxidizing agent .…”
Section: Introductionmentioning
confidence: 99%
“…Indian meal moth in pistachios, 14 and Oryzaephilus surinamensis in dried figs. 15 Ozone has potential to reduce the toxic effect of insecticides in food products by acting as a strong oxidizing agent. 16 Results from earlier studies showed that ozone results in discontinued respiration in insects and reacts with proteins, DNA and double bonds of polyunsaturated fatty acids, causing increased cellular lesions and death.…”
Section: Introductionmentioning
confidence: 99%